Paleodietary reconstruction using stable isotopes and abundance analysis of bovids from the Shungura Formation of South Omo, Ethiopia. Issue 88 (November 2015) - Negash, Enquye W.; Alemseged, Zeresenay; Wynn, Jonathan G.; Bedaso, Zelalem K.
Abstract: Preservation of the stable carbon isotopic composition of fossil tooth enamel enables us to estimate the relative proportion of C3 versus C4 vegetation in an animal's diet, which, combined with analysis of faunal abundance, may provide complementary methods of paleoenvironmental reconstruction. To this end, we analyzed stable carbon isotopic composition (δ 13 C values) of tooth enamel from four bovid tribes (Tragelaphini, Aepycerotini, Reduncini, and Alcelaphini) derived from six members of the Shungura Formation (Members B, C, D, F, G, and L; ages from ca. 2.90–1.05 Ma (millions of years ago) in the Lower Omo Valley of southwestern Ethiopia. The bovids show a wide range of δ 13 C values within taxa and stratigraphic members, as well as temporal changes in the feeding strategies of taxa analyzed throughout the middle to late Pliocene and early Pleistocene. Such variation suggests that the use of actualistic approaches for paleoenvironmental reconstruction may not always be warranted. Alcelaphini was the only taxon analyzed that retained a consistent dietary preference throughout the sequence, with entirely C4 -dominated diets. Reduncini had a mixed C3 /C4 to C4 -dominated diet prior to 2.4 Ma, after which this taxon shifted to a largely C4 -dominated diet. Aepycerotini generally showed a mixed C3 /C4 diet, with a period of increased C4 diet from 2.5 to 2.3 Ma. Tragelaphini showed a range of mixed C3 /C4 diets, with a median value that was briefly nearer the C4 end member from 2.9 to 2.4 Ma but was otherwise towards the C3 end member. These isotopic results, combined with relative abundance data for these bovids, imply that the environment of the Lower Omo Valley consisted of a mosaic of closed woodlands, with riverine forests and open grasslands. However, our data also signify that the overall environment gradually became more open, and that C4 grasses became more dominant. Finally, these results help document the range and extent of environments and potential diets that were available to the four hominin species encountered in the Shungura sequence.